Genealogi Gerakan Ikhwan Al Muslimin dan Al Qaeda di Timur Tengah - Rijal Mamdud (Indonesia Center for Middle East Studies, 2018)
Historically, the rise of terrorism by radical Islamic groups in the Middle East has itsroots in the spirit of resistance to Western colonialism in the early nineteenth century.There are two movements that have a big influence and inspire the emergence ofsimilar movements in the Middle East, the Ikhwan Al Muslimin (IM) and Al Qaeda (AQ).This paper examines the roots of IM and Al Qaeda movements, and how the powerknowledgerelation takes place. The theory used in this research is genealogy whichseeks to examine the historical aspect and its relation to the formulation of powerand politics; as well as the theory of Islamism, namely describing aspects of Islamicideology, Islamic political movements, and socio-economic aspects. The findings ofthis article explain that IM and AQ have historically been rooted in the resistancemovement against the West. Sayyid Qutb’s thoughts became the initial inspirationfor the radicalization of IM activists, such as Muhammad Faraj, Ayman Al Zawahiri,and Osama bin Laden, so they built more extreme militias, such as Al Jihad and AlQaeda. IM was originally a social organization and eventually involved in practicalpolitics. Methods of Islamic movement based on cultural approach make IM widelyaccepted by Egyptian society, so that ever managed to win in election and be in elitecircle of power. On the contrary, AQ is conducting a resistance movement againts theWest as well as governments in Muslim countries that are considered anti-Islamic bythe method of terror, so it always marginal in public opinion of Muslim society.